Audience Involvement in How Celebrities Communicate within Social Networks - Siudikienė, Daiva (Information & Media, 2018)
[full article and abstract in Lithuanian; abstract in English]This article presents theoretical and empirical research that aims to analyze the techniques for increasing audience engagement in celebrity communication. It was discussed which part of the followers across social networks could be defined as the fans of a given celebrity. The paper discusses the identification of the fans among the total followers of a celebrity. In discussing the patterns of follower engagement, the aspects of emotional connectivity should be emphasized: warm appeals to followers, questions for the mutual discussions, provocations, hints, and intrigues, all utilized in order to pique the audience’s curiosity, asking opinions on various issues, publishing motivational, inspirational stories, giving presents, organization of contests, thanks for being together at concerts and giving support, compliments to supporters, etc. In addition to the emotional value, it is possible to highlight a practical value of the celebrity’s announcements to their followers in terms of job offers, opportunities for participation in video shoots, the sharing of concessions, invitations to events, closed parties, etc.The empirical research has revealed that the followers are not necessarily the fans of celebrities. In analyzing the feedback of the followers, certain groups become particularly obvious: fans, non-fans, and anti-fans, as stated by J. Grey. Not only constructive statements can be seen in the comments section, but also objections to the position expressed by the celebrity, and even extremely negative feedback (those who are questioning the celebrity’s talent, morality, popularity, etc.). Fans obviously are the most active part of the followers, who mostly respond to the celebrity’s messages. They are characterized by their active participation in contests, constant commentaries, open and sincere admiration of the celebrity and all they have done, strong support in all of their decisions, resentment expressed regarding any unfriendly comments, often acting as a defensive shield against the unfriendly followers.Fans actively follow the celebrities’ lives, welcoming the various personal, national, and state celebrations, expressing their joy in the new stage of activity and achievements, demonstrating a deeper knowledge of past work and previous achievements, incorporating celebrity-created photoclays that exaggerate the strengths of the celebrities.
Keywords: celebrity; celebrity culture; media; social networking sites; audience activity; audience engagement; followers; friends; fans